Gerakan sadar lingkungan melalui sosialisasi dan pelatihan pengelolaan limbah cair rumah tangga dukuh jongso - Erika Rian Prahastiwi; Eny Wiwin Kartikaningsih; Khoirunnisa Khoirunnisa; Danang Puji Atmojo; Nira Fery Thania; Adinda Natasya Ayodya (Lentera Negeri, 2021)
Community activities during the pandemic due to the stay at home policy resulted in an increase in the remaining results of activities. As a result, untreated household wastewater will have a negative impact on the surrounding waters and can become a source of disease for the community. The main purpose of this service is to educate and provide skills to the community to treat household wastewater in Jongso Hamlet, Wotan Village. The main material used for wastewater treatment is alum. This is because alum is a coagulant that can bind impurities in water. This service activity is carried out by socializing through online audio-visual media, namely Youtube, while the training is carried out directly at the stage of processing household liquid waste to the Dukuh Jongso community, and activity evaluation indicators are based on participant responses to socialization and training. The results of the implementation showed that the participants were enthusiastic in the socialization and training. This activity is also effective in educating the public, especially about public awareness of the surrounding environment. It is hoped that the community will continue to be committed to improving their knowledge and skills in protecting the surrounding environment. The community care movement for the surrounding environment is expected to continue to be applied independently and disseminated to other communities.